Beyond the Lesion: Back to High Fidelity DNA Synthesis - Kaszubowski, Joseph D.; Trakselis, Michael A. (Frontiers in Molecular Biosciences, 2022)
High fidelity (HiFi) DNA polymerases (Pols) perform the bulk of DNA synthesis required to duplicate genomes in all forms of life. Their structural features, enzymatic mechanisms, and inherent properties are well-described over several decades of research. HiFi Pols are so accurate that they become stalled at sites of DNA damage or lesions that are not one of the four canonical DNA bases. Once stalled, the replisome becomes compromised and vulnerable to further DNA damage. One mechanism to relieve stalling is to recruit a translesion synthesis (TLS) Pol to rapidly synthesize over and past the damage. These TLS Pols have good specificities for the lesion but are less accurate when synthesizing opposite undamaged DNA, and so, mechanisms are needed to limit TLS Pol synthesis and recruit back a HiFi Pol to reestablish the replisome. The overall TLS process can be complicated with several cellular Pols, multifaceted protein contacts, and variable nucleotide incorporation kinetics all contributing to several discrete substitution (or template hand-off) steps. In this review, we highlight the mechanistic differences between distributive equilibrium exchange events and concerted contact-dependent switching by DNA Pols for insertion, extension, and resumption of high-fidelity synthesis beyond the lesion.